2019
DOI: 10.3390/ijerph16224498
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived Accessibility, Satisfaction with Daily Travel, and Life Satisfaction among the Elderly

Abstract: People are living longer than they did previously, and the proportion of older people is increasing worldwide. This rapid development will have implications for the transport system, in general, and for travel behavior and accessibility to daily activities, in particular. In recent years, both research and politics have drawn the attention of the public to issues affecting the opportunities of the elderly to participate in everyday life. The debate has so far mostly focused on health issues, with limited work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 44 publications
(61 reference statements)
2
38
0
3
Order By: Relevance
“…Contrary to other findings [25] where no age differences for perceived accessibility were detected, we found that perceived accessibility increases with age for our sample. A possible explanation for increased perceived accessibility among elderly age groups, despite the age-related decline in physical prerequisites for easy travel, is offered by Lättman et al [43] and poses that the elderly travel less and to fewer destinations than younger people do, and thus are less dependent on transport systems. Our findings, and recent findings among other researchers [20], imply though that subjective factors, such as attitudes and functionality, may be better predictors of perceived accessibility than sociodemographic factors, such as age.…”
Section: General Findings In Light Of the Structural Model And The Hymentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to other findings [25] where no age differences for perceived accessibility were detected, we found that perceived accessibility increases with age for our sample. A possible explanation for increased perceived accessibility among elderly age groups, despite the age-related decline in physical prerequisites for easy travel, is offered by Lättman et al [43] and poses that the elderly travel less and to fewer destinations than younger people do, and thus are less dependent on transport systems. Our findings, and recent findings among other researchers [20], imply though that subjective factors, such as attitudes and functionality, may be better predictors of perceived accessibility than sociodemographic factors, such as age.…”
Section: General Findings In Light Of the Structural Model And The Hymentioning
confidence: 99%
“…In such a scenario, there is a need to lift those attributes that are important to public transport-related perceived accessibility, such as quality aspects and travel safety perceptions, in order to maintain a level of perceived accessibility that offers satisfactory possibilities to engage in daily activities. In any case, as perceived accessibility recently has been linked to life satisfaction [43], it appears important not only to examine the role of perceptions of accessibility for modal choice but to also further explore the effect of modal choice on perceived accessibility.…”
Section: General Findings In Light Of the Structural Model And The Hymentioning
confidence: 99%
“…Regarding the research on the accessibility of healthcare services, most scholars only focus on the accessibility of healthcare services facilities for the older adults [5][6][7]. Although some scholars have also paid attention to the accessibility of intelligent services [8], network service [9], public service [10], life satisfaction [11], etc., all are based on the realized accessibility, ignoring the potential opportunities and willingness of the older adults to use healthcare services. This not only hinders the access to healthcare services, but also is not conducive to stimulate the healthcare service market.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical model of the relationship between perceived accessibility, satisfaction with travel, and life satisfaction is presented by Lättman, Olsson Friman and Fujii [4]. These researchers argue that older people's perceived possibilities of accessing activities are closely linked to their wellbeing.…”
mentioning
confidence: 99%
“…These researchers argue that older people's perceived possibilities of accessing activities are closely linked to their wellbeing. Lättman et al [4] define perceived accessibility in terms of perceived possibilities of accessing activities that are of importance to everyday life, or in terms of "how easy it is to live a satisfactory life considering how people travel". Empirical testing of the model showed that perceived accessibility influences travel satisfaction, in that a higher degree of perceived accessibility (ease of travel, possibilities of traveling, and access to preferred activities) increases satisfaction with travel, while a lower degree of perceived accessibility decreases satisfaction with travel.…”
mentioning
confidence: 99%